1991
DOI: 10.1016/0014-5793(91)80167-2
|View full text |Cite
|
Sign up to set email alerts
|

Specific activation of Gs by synthetic peptides corresponding to an intracellular loop of the β‐adrenergic receptor

Abstract: Peptide= correspondinR, to the amino tLcid ~equenee or the hamster/~=.~drenergi¢ receptor If/eAR.) were synthesized and their ability to activate purified O.proteins determined. Two peptides. ¢omprismll the N, and C-terminal I$ m'nino arid= of the putative third intraeellular loop region or the p~AR were found to aetivale the G.protein O, but not to activate a preparation of G,/G,. Other p~ptides ¢orre~pondin= to the intern=l portion= of this loop and the C.terminal lab region fitiled to activate either G.prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 18 publications
2
49
0
Order By: Relevance
“…In addition, it is possible that the sequence proximal to the QKIDKSEGF motif also contributes to G s activation. Indeed, previous studies demonstrated that peptides from the proximal portion of the hamster ␤ 2 AR ICL3 are direct activators of nucleotide exchange on G s (52). The most effective peptide from these studies was VYS-RVFQVAKRQLQK, which is proximal to the QKIDKSEGF motif.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, it is possible that the sequence proximal to the QKIDKSEGF motif also contributes to G s activation. Indeed, previous studies demonstrated that peptides from the proximal portion of the hamster ␤ 2 AR ICL3 are direct activators of nucleotide exchange on G s (52). The most effective peptide from these studies was VYS-RVFQVAKRQLQK, which is proximal to the QKIDKSEGF motif.…”
Section: Discussionmentioning
confidence: 98%
“…Although previous studies used unmodified peptides that have a limited ability to cross the cell membrane (52), the N-terminal palmitoylation and C-terminal amidation of a pepducin enable membrane incorporation and effective delivery to the intracellular surface of the cell membrane (18). For ICL3-8, this provides a means of targeting it to the site of action as G s is localized to the intracellular surface of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…From the assignment of Lys-290 to the helical part this residue can be considered either as an integral part of the membrane or as part of a cytoplasmic extension of the transmembrane helix [2,27].…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis studies have demonstrated that sequences immediately carboxyl-terminal to Cys-265 are important for G-protein coupling (6 -10), and mutation of the nearby Leu-272 leads to constitutive activation (11). In addition, synthetic peptides representing sequences from the carboxyl-terminal portion of IC3 are capable of directly stimulating G proteins (12)(13)(14). Therefore, a f luorophore covalently bound to Cys-265 is well positioned to detect agonistinduced conformational changes relevant to G-protein activation.…”
mentioning
confidence: 99%